NEW REGENERATOR DESIGN FOR REGENERATION OF RAW COTTON VOLES FROM NON-GINNED SEEDS (Innovative Technologica: Methodical Research Journal, 2023)
This article provides information about the operating parameters and efficiency of regeneration, a new design of a regenerating device for under-ginned seeds, before the linting process.